The Reflective Skill Worksheet: A Semi-Structured Approach for Critiquing, Framing and Delivering Feedback - Andrew Mutnick; Michael Devlin; Dorene Balmer; Boyd Richards (Association of American Medical Colleges, 2010)
Abstract Introduction Within medical education, there is an increasing value in having learners' reflect upon their clinical experiences. Although this value is borne out of both empiric and theoretical evidence, there is scant published material that aids teachers in guiding and enhancing learners' reflective skills. This Reflective Skill Worksheet (RSW), adapted and modified from a model espoused in the teacher education literature, is intended for usage by teachers and preceptors who are called upon to respond to students' narrative reflections around a single clinical encounter. This resource includes the Reflective Skill Worksheet along with a sample clinical reflection and worksheet pair that illustrate this tool's practical use. Methods The RSW was introduced to core faculty in our school's Clinical Practice course and preceptors in our third-year transclerkship course, which focuses on a physician role and reflective practice and requires students to reflect on their clinical encounters. The RSW presents a rubric which encourages and guides facilitators to assess the depth and breadth of narrative clinical reflections across the dimensions of description (e.g., How clearly the write expressed the central theme or dilemma?), comparison (e.g., To what extent the writer included relevant perspectives?), personal engagement (e.g., How intense and apparent the writer is engaged with the reflection?), and critical review (e.g., Did the writer experience a change in position or had a previous belief deepened?). Students are then given feedback based on the four dimensions of the RSW. Results Preceptors greeted the introduction of the RSW with great enthusiasm for its simplicity and appreciation for the ease of use. Comments elicited during a focus group of students who had reflections evaluated by the RSW stated that their experiences were largely positive and encouraging. The RSW was also introduced to a national audience of medical educators at the 2008 AAMC Conference in San Antonio, Texas and the 2010 Pediatric Academic Society in Vancouver, Canada. Participants' utilization of the worksheet's semi-structured approach produced concordant assessment across multiple sample reflective essays. This speaks to the resource's straightforwardness and hints at its reliability. Many workshop participants stated that the worksheet facilitated their ability to develop specific feedback when applied to the sample reflections provided. Discussion Positive feedback from both students a preceptors suggests that this tool and technique would generalize to a wider group of teachers and learners in an effort to enhance reflective skills.